The potential for repurposing α2-adrenoceptor agonists and noradrenaline uptake1 inhibitors in the management of septic shock - Benyamen, Julian (2024)
Background: Septic shock is a life-threatening condition characterised by consistent hypotension caused by vasoplegia, endothelial dysfunction, and abnormal nitric oxide (NO) metabolism, leading to multiple organ failure. It affects more than 48 million people globally each year and is associated with approximately 11 million deaths. The guidelines from the Surviving Sepsis Campaign (SSC) describe early fluid resuscitation and antibiotics as the fundamental treatments of sepsis. However, a large number of patients with sepsis still progress to septic shock with unstable haemodynamic responses, necessitating the use of vasopressors to enhance organ perfusion. Noradrenaline (NA) is the first choice to be used in intensive care units (ICUs), but high doses of NA might lead to adverse cardiac complications such as tachyarrhythmia, peripheral ischaemia, and immunosuppression. A strategy of combining NA with other vasoactive agents has been recently proposed to reduce the required doses or the time spent on NA infusion and to improve the outcomes of sepsis patients in ICU.